An effective system of material incentives for pedagogical workers of professional education - E. I. Velmisova (Путеводитель предпринимателя)
The article describes the main problems in the system of stimulation of work of pedagogical workers of University, as well as secondary and primary professional education, the necessity of creation of effective system of stimulation and motivation of teachers on the basis of an effective contract.